Competition Measurement of Hospitals in Poland: the Herfindahl-Hirschman Index Approach - Rój, Justyna (Ekonomika, 2016)
The purpose of this study was to measure the competition level of general hospitals in Poland. The Herfindahl-Hirschman Index (HHI) was used to investigate the concentration level of the general hospital sector in Poland, which is treated in the literature as a proxy of competition. To understand how general hospitals’ market has been structured and thus competitive, the data for general hospitals spanning all Poland for the period of 2005-2013 were collected. The concentration of hospitals was measured in each of the 16 provinces in Poland based on the aggregated data at the counties level. Data are collected from the public statistical system. The HHI indices support the assertion that in the period of analysis the entire general hospitals’ sector in Poland has been on average moderately concentrated and thus, moderately competitive with the growing tendency to higher concentration and less competition. Moreover, the concentration of hospitals’ services is diversified across the provinces and regions of Poland and it is quite uneven. The analysis also shows that changes in the health care market, which took place in the analysed period, especially statutory changes regarding hospitals in 2011, affected the level of concentration and thus competition. Including this introduction, this paper is organized into six sections. Section 2 outlines the Polish health care reforms especially those applying to hospitals. Section 3 and 4 presents the concept of empirical research, such as data and method. Section 5 provides results of empirical research and section 6 concludes.